A metamodel specification tool based on description logic and XML-DATA - Nicolle, Christophe (Revista Colombiana de Computación, 2001)
Interoperation of heterogeneous and autonomous information systems has traditionally been hampered by semantic differences intheir data models. Keywords: Cooperation, extensibility, metamodel, translators, description logic, xml-data.